OPTIMAL PLANNING OF OPERATIONAL MODES OF GAS PIPELINE TRANSPORTATION SYSTEMS UNDER MULTICRITERION CONDITIONS - Грудз, Ярослав Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Methods for construction of areas of allowable modes of compressor stations of main gas pipelines as well as construction of marginal areas of energy consumption are presented. It is proposed to use them for optimization of operational modes of gas pipeline transportation system.